Design of Pico-Hydro Power Plant with Monitoring System Based on Internet of Things - Fadhillah Hazrina; Purwiyanto Purwiyanto (Electrical Engineering Dept, Engineering Faculty, Universitas Andalas, 2022)
Currently the electrification ratio in Banyumas Regency is around 79%. This means, of the 1.7 million residents of Banyumas Regency, only around 21% have not enjoyed PLN electricity. Those whose homes have not yet had electricity are on average residents who are on the slopes of the mountain slopes, and some residents in several groves in remote areas in Banyumas Regency which are very far from the PLN electricity network. This problem can be overcome by providing electrical energy by utilizing renewable alternative energy, one of which is micro hydro or pico hydro power plants on an individual or residential scale. Therefore, this research designed a simulation of a pico hydro power plant using a Pelton turbine which is expected to be able to provide benefits to the general public, this tool is equipped with remote monitoring using Google Firebase based on the Internet of Things which can be monitored via the Android application for monitoring Voltage, current and power use the INA219 sensor which has been programmed on Arduino Uno and Node MCU ESP8266. This tool uses a 12-24 Volt DC generator, produces DC electricity which is stored in a 12 Volt 5 Ah battery which is then converted using an inverter to become AC electricity. In this test using a 5 Watt AC lamp load, the battery voltage which was initially 12.6 Volts was reduced to 9.9 Volts, the lamp load was able to light up for 1 hour. In measuring the voltage and current, the generator produces an average voltage of 15.9 Volts and a current of 50.2 mA.